Mechanisms underlying TDP-43 pathology and neurodegeneration: An updated Mini-Review - Nilaver, Benjamin I.; Urbanski, Henryk F. (Frontiers in Aging Neuroscience, 2023)
TAR DNA binding protein 43 kDa (TDP-43) plays an important role in several essential cell functions. However, when hyperphosphorylated and ubiquinated, TDP-43 contributes to the development of various brain diseases including amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD), and limbic predominant age-related TDP-43 encephalopathy (LATE). Recent investigations into the individual components of TDP-43 pathology show how broader TDP-43 dysfunction may precede these disease end states, and therefore could help to explain why TDP-43 dysfunction continues to be implicated in a rapidly expanding category of neurodegenerative diseases. The literature reviewed in this article suggests that dysregulation of TDP-43 initiated by some environmental and/or genetic insults can lead to a snowballing dysfunction across the cell, involving impaired gene expression, mRNA stability, as well as the function and coordination of those pathways directly regulated by TDP-43. Furthermore, the hallmarks of TDP-43 pathology, such as hyperphosphorylation and insoluble cytoplasmic accumulation of the protein may actually be artifacts of an upstream impairment in TDP-43’s normal function. Overall, the present article summarizes current knowledge regarding TDP-43’s normal and pathological cell functions and sheds light on possible mechanisms that underlie its causal role in neurodegeneration.